Impossibilità di pensare Dio non esistente : il Proslogion di Anselmo d'Aosta come applicazione implicita dei moderni procedimenti di logica aletica - Livi, Antonio (Sapientia, 2009)
The most famous Anselm of Canterbury’s work, the Proslogion, has been object of many different interpretations from the Middle Ages to our times. Almost all those interpretations deal with the sense and the goal of what Anselm called an «unum argumentum» for proving that God exists. Unfortunately, all major commentaries on Anselm’s argument ―especially those formulated by modern and contemporary philosophers― are founded on an interpretation of it as an «ontological argument». Now, this interpretation is quite wrong, since it implies the theory of «ideae innatae», a doctrine which is typical of Descartes but could not absolutely be attributed to Anselm. In this article a new interpretation is proposed. It is founded on the acknowledgement of the real intention that moved Anselm to write his work, whose former title was Fides quaerens intellectum, that is, Christian faith needs understanding. Anselm was concerned with the theological search of a deeper and more clear knowledge of what divine revelation says about God’s existence and God’s attributes, like potency, wisdom, mercy, and justice. Anselm realizes that divine truth is more and more comprehensible if the believer takes into account the very reasons of his believing and uses his reason for making his belief stronger. So, just in the first age of Scholasticism, using pure reason in the theological search is recognized as absolutely necessary for Christian faith. The teaching of Thomas Aquinas in the thirteenth century will be only a development of Anselm’s genial intuition.